1991
DOI: 10.1038/353043a0
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of G-protein subtypes to specific receptors inducing inhibition of calcium currents

Abstract: The inhibition of voltage-dependent Ca2+ channels in secretory cells by plasma membrane receptors is mediated by pertussis toxin-sensitive G proteins. Multiple forms of G proteins have been described, differing principally in their alpha subunits, but it has not been possible to establish which G-protein subtype mediates inhibition by a specific receptor. By intranuclear injection of antisense oligonucleotides into rat pituitary GH3 cells, the essential role of the Go-type G proteins in Ca(2+)-channel inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
239
2
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(261 citation statements)
references
References 46 publications
13
239
2
5
Order By: Relevance
“…In this context, it is worth noting that a total of 800 di erent abgcon®gurations are theoretically possible and it is likely that some of these con®gurations de®ne the speci®city of G protein interactions. The ®ndings that the Gbgsubunit con®guration can confer speci®city to the signaling pathways regulated by Ga o also supports this view (Kleuss et al, 1991;Kleuss et al, 1992).…”
Section: Diversity Of G Protein Signalingmentioning
confidence: 68%
“…In this context, it is worth noting that a total of 800 di erent abgcon®gurations are theoretically possible and it is likely that some of these con®gurations de®ne the speci®city of G protein interactions. The ®ndings that the Gbgsubunit con®guration can confer speci®city to the signaling pathways regulated by Ga o also supports this view (Kleuss et al, 1991;Kleuss et al, 1992).…”
Section: Diversity Of G Protein Signalingmentioning
confidence: 68%
“…No such differences are known for the classical PTX-sensitive inhibitory G a subunits, G i a1-3 (Taussig and Gilman 1995;Sunahara et al 1996). These regulatory patterns indicate that the functional significance of heterogeneity at the level of inhibitory G proteins lies not exclusively in conferring specificity to receptor/G coupling (Kleuss et al 1991;Leaney et al 2000). Instead, they open the opportunity for the existence of multiple inhibitory AC pathways within a single cell.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the signal transduction pathway mediating tolerance/dependence is hampered by the ability of ORs to activate multiple inhibitory G proteins and intracellular effector systems (Gudermann et al 1992). Several experimental approaches have been employed to elucidate the specificity of signal transduction cascades in situ, such as application of site-directed anti-G protein antibodies (Simonds et al 1989), antisense strategies (Kleuss et al 1991), and over-expression of genetically modified PTXresistant inhibitory G a subunits (Leaney et al 2000). However, each of these approaches failed to define specific inhibitory AC signalling pathways most likely because of a pronounced functional redundancy between inhibitory G a subunits (Tang et al 1991;Sunahara et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Also, SOM-14 could hyperpolarize cortical neurons of the CNS. This is made possible by increasing K + current (Wang et al, 1989) and inhibiting a voltage-dependent Ca 2+ current via a GTP-binding protein (Dichter et al, 1990;Kleuss et al, 1991). It was found that SOM inhibited the GLU-evoked response, indicating its inhibitory action on the excitability of postsynaptic neuron.…”
Section: Discussionmentioning
confidence: 99%